PENGGUNAAN MEDIA SOSIAL APLIKASI LITA DALAM MEMBENTUK PERSONAL BRANDING SEBAGAI GAMERS WANITA - Leoni Oktavia Maharani; Hanafi Hanafi (Universitas Teuku Umar, 2022)
Personal Branding for an individual who is undergoing a career is needed so that it can be differentiated, attractive and easier to remember by consumers or their clients. Today, media convergence has triggered many innovations resulting from the existence of social media, as now social media in the form of applications can be the right means to form personal branding. This study aims to analyze the personal branding carried out by female gamers who use the Lita application to open services for friends to play paid games. This study will try to describe more clearly the process of forming personal branding based on the components of personal branding proposed by (Parengkuan & Tumewu, 2014). Informants as female gamers who open services for friends to play paid games through the Lita application, of course, must have personal branding in order to differentiate themselves from other gamers who open similar services on the Lita application. The results found that the informants succeeded in implementing the components of personal branding, this can be seen from the character, appearance and reciprocity felt by consumers in the reviews of informants' comments on each informant's account on the Lita application.